Postoperative pain after SWEEPS, PIPS, sonic and ultrasonic-assisted irrigation activation techniques: A randomized clinical trial - Erkan, Erhan; Gündoğar, Mustafa; Uslu, Gülşah; Özyürek, Taha (Springer, 2022)
To investigate the efficacy of a new laser irrigation activation system [shock wave-enhanced emission photo-acoustic streaming (SWEEPS)] in terms of postoperative pain after primary root canal treatment compared with other techniques, namely photon-induced photo-acoustic streaming (PIPS), sonic system with EDDY, passive ultrasonic system (PUI), and manual dynamic activation (MDA). Two hundred patients with symptomatic irreversible pulpitis in mandibular premolar teeth were enrolled and randomly allocated to five different irrigation activation groups (n = 40) after chemo-mechanical root canal preparation. For irrigation activation, the SWEEPS and PIPS tips were attached to the Er-YAG laser system in the respective groups, while the Irrisafe tip was used in the PUI group and the EDDY tip in the sonic group. In the MDA group, irrigation was agitated with the master gutta-percha cone. At postoperative hours 8, 24, and 48 and on day 7, pain intensity was evaluated using the 10-mm Visual Analog Scale (VAS) and analgesic intake was recorded. The Kruskal–Wallis test was used to analyze the VAS scores, and pain prevalence and analgesic intake were examined with the Pearson’s chi-square test at the 5% significance level. The PIPS and SWEEPS groups had the lowest level and prevalence of pain when compared to the remaining groups (P < 0.001). The PUI, sonic and MDA groups did not differ in terms of pain scores at hours 8 and 48 (P > 0.05). On day 7, the highest score and pain prevalence were recorded in the MDA group (P < 0.001). There was no difference between the groups in terms of analgesic intake (P > 0.05). Laser-activated irrigation systems provided lower postoperative pain scores and levels compared to the other activation systems. The MDA group had the highest pain scores and incidence at the end of the seventh day.
Keywords: Analgesic Intake; EDDY; Irrigation Activation; PIPS; SWEEPS